YO SOY... : the participation of names and surnames in the defense of rights - Villalta , Carla; Lopes Murillo, Aline (Universidade de Brasília, 2021)
This article examines, firstly, civil registration laws and bureaucratic procedures to restore the identity of the grandchildren of the Abuelas of Plaza de Mayo in Argentina. Secondly, it seeks to understand the meanings of names and surnames in the construction of identity and the way in which these elements are mobilized to constitute person, memory and to defend rights.